Kato Malereng: Indirect Speech Ethics in Maintaining Dignity and Social Hierarchy in Minangkabau Society - Rozalvino Rozalvino; Bambang Sunarto; Andar Indra Sastra; Pande Made Sukerta (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze kato malereng as a form of indirect speech ethics in maintaining dignity and social hierarchy within Minangkabau society. In Minangkabau culture, language functions not only as a means of communication but also as a system of values that regulates social relationships and preserves community harmony. This research employs a descriptive qualitative approach using a library research method to examine cultural communication practices within the kato nan ampek system. Data were collected through the analysis of relevant literature on communication ethics, cultural values, and the social structure of Minangkabau society and were analyzed using descriptive-interpretative techniques to identify the forms, functions, and social meanings of kato malereng. The findings indicate that kato malereng functions as a cultural communication mechanism that preserves dignity, prevents conflict, and strengthens social cohesion through the use of figurative and polite language. Despite adjustments in modern communication contexts, the values of politeness and respect embedded in kato malereng remain relevant as communication guidelines. Therefore, kato malereng represents a form of local wisdom that contributes to the preservation of cultural values and social stability in contemporary society.